MANAGEMENT CONTROL FOR CREATING INNOVATION IN TEACHING METHODS IN ENTREPRENEURSHIP-BASED UNIVERSITIES - Bernardus, Denny (Universitas Brawijaya, Indonesia, 2018)
Innovation is one of the most important strategies for gaining a competitive advantage, especially for a new organization entering the industry that has been around for quite a long time. To ensure the strategy can be executed, management control has an important role in the implementation of the strategy. This study aims to investigate the role of management control in creating innovative teaching methods in a study program at a Private University. To answer the research question, the researcher used a single case qualitative study method. The method of data collection has been done through interviews, documentation, and observation. The results of this study found that management control mechanisms play a major role in creating innovative teaching methods. Although some weaknesses and obstacles were found, the teaching methods created could inspire students to achieve the objectives of the study program.